Applicability of Hooke’s and Jeeves Direct Search S olution Method to Metal cutting [Turning] Operation. - Mr. G. S. Kirgat; Prof. A. N. Surade (International Journal of Innovations in Engineering Research and Technology, 2021)
Role of optimization in engineering design is prominent one with the advent of computers. Optimization has become a part of computer aided design activities. It is prima rily being used in those design activities in which the goal is not only to achieve just a feasible design, but also a des ign objective. In most engineering design activities, the design objective could be simply to minimize the cost of production or to maximize the efficiency of the production. An optimization algorithm is a procedure which is executed it eratively by comparing various solutions till the optimum or a satisfactory solution is found. In many industri al design activities, optimization is achieved indirectly by comparing a few chosen design solutions and accept ing the best solution. This simplistic approach never guarantees and optimization algorithms being with one or more d esign solutions supplied by the user and then iteratively check new design the true optimum solution. There ar e two distinct types of optimization algorithms which are in use today.